Enhanced Particle Swarm Optimization Algorithms With Robust Learning Strategy For Global Optimization - Lim, Wei Hong (2014)
Particle Swarm Optimization (PSO) is a metaheuristic search (MS) algorithm inspired by the social interactions of bird flocking or fish schooling in searching for food sources. Pengoptimuman Kawanan Zarah (PSO) merupakan satu algoritma pencarian metaheuristik (MS) yang diinspirasi oleh interaksi sosial kumpulan burung atau kawanan ikan semasa pencarian sumber makanan.